Effects of Glomus fasciculatum, Azotobacter chroococcum and Vermicompost Leachate on the Production and Quality of Tomato Fruit - Alejandro Alarcón-Zayas; Luis Guillermo Hernández-Montiel; Diana Medina-Hernández; Edgar Omar Rueda-Puente; Wilson Geobel Ceiro-Catasú; Ramón Jaime Holguín-Peña (Microbiology Research, 2024)
Arbuscular mycorrhizal fungi, plant-growth-promoting bacteria (PGPB) and vermicompost constitute important environmental and economic resources for improving the production and quality of tomato fruits. The present research aims to determine the single and combined effect of Glomus fasciculatum (Gf) fungus, Azotobacter chroococcum (Azot), PGPB and vermicompost leachate (VL) organic fertilizer on the yield and quality of tomato fruit. Thus, an open-field experiment was established with seven treatments, a control and three replicates. Total soluble solids, vitamin C, acidity, fruit mass and fruit diameter were evaluated as fruit quality variables; the yield was recorded and estimated in tons per hectare−1. The results showed that Gf, Azot and VL were effective in promoting tomato yield and fruit quality. As a trend, the triple combination (Gf + Azot + VL) evidently obtained the highest values of total soluble solids, vitamin C and fruit acidity. The range of improvement concerning the fruit size was 66.6% (single treatment) compared to 78.5% (triple combination). The maximum yield of 54.5 t/ha−1 was recorded for the Gf + Azot + VL combination. Therefore, G. fasciculatum, A. chroococcum and VL are considered useful as organic alternatives for open-field tomato biofertilization programs in tropical countries.